A macroporous weak base anion exchange resin with high abrasion resistance and high permeation intensity and a preparation method thereof
Patent Information
- Application Number
- CN202511881142.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-15
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2045-12-15
AI Technical Summary
但目前树脂存在耐磨渗强度弱、洗脱困难等缺陷,同时阴离子交换树脂对糖液中Ca2+、Mg2+等高价阳离子敏感,易被这些离子毒化而失活
(1)本发明通过丙烯酸和苯乙烯等基团的共聚反应,在苯乙烯树脂骨架中引入柔性的丙烯酸基团,提高了树脂的耐磨渗强度(耐磨渗强度是表征离子交换树脂机械强度的关键指标,反映树脂抵抗逆洗、混合及反复膨胀收缩等作用导致颗粒破裂的能力。长期使用中需选择兼具机械强度与物理化学稳定性的树脂类型。测定时通过周期性酸、碱处理产生渗透力,结合瓷球滚磨施加压力与摩擦力。经处理的树脂经烘干后分离破碎颗粒,以渗磨圆球率(保持球状未破碎颗粒的比例)定量表征耐磨性能;耐磨是在溶液下测试耐磨,耐磨测试的性能称为耐磨渗强度)。同时以氮化硼粉末为核构筑复合型苯乙烯树脂,可以发挥氮化硼优异的润滑特性,进一步提升树脂的耐磨渗强度。
Smart Images

Figure CN121628021B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a macroporous weak base anion exchange resin with high wear and permeation resistance and its preparation method, which is particularly suitable for the decolorization and desalination processes in sugar processing and belongs to the field of functional polymer materials technology. Background Technology
[0002] With the improvement of living standards, the consumption of high-quality sugar is increasing. In the sugar production process, decolorization and purification are crucial steps, and the quality of the decolorization directly affects the quality of the sugar product. Traditional syrup treatment mainly uses materials such as activated carbon, but the treatment effect is unsatisfactory. Ion exchange has advantages such as a wide decolorization range, high decolorization capacity, and reusability, and has been widely used in sugar production. The resin commonly used for sugar decolorization is a macroporous, strongly basic styrene anion exchange resin. Patent CN2025104911191 discloses a macroporous adsorption resin for sugar decolorization, which is a macroporous adsorption resin prepared using styrene, divinylbenzene, and methyl acrylate as polymer monomers. This resin has a suitable specific surface area and pore size, which can better adsorb large-molecule natural pigments, and also has certain mechanical properties, allowing for multi-cycle use. However, current resins have defects such as weak abrasion resistance and difficulty in elution. Furthermore, anion exchange resins have limitations in their ability to effectively remove Ca2+ from sugar solutions. 2+ Mg 2+ High-valence cations are sensitive, and sugars are easily poisoned and deactivated by these ions. In addition, sugars must undergo desalination after decolorization, which requires additional treatment with cation exchange resins, increasing the complexity and cost of the process. Summary of the Invention
[0003] In view of the shortcomings of the prior art, the object of the present invention is: This invention provides a macroporous weak base anion exchange resin with high wear resistance and permeability. This resin is suitable for decolorization and desalination processes in the food processing and food fermentation industries, and is particularly suitable for decolorization and desalination of xylitol and sucrose.
[0004] Meanwhile, this invention provides a method for preparing a macroporous weakly basic anion exchange resin with high abrasion and permeation resistance. This method utilizes a nitrogen-containing heterocyclic compound to modify hexagonal boron nitride. The modified hexagonal boron nitride is added to an ion exchange resin suspension polymerization system containing acrylic acid as a spacer group and triallyl isocyanurate as a polar crosslinking group to obtain resin white spheres. Finally, high abrasion and permeation resistance macroporous weakly basic anion exchange resin is obtained through chloromethylation and tertiary amination. This resin possesses excellent abrasion and permeation resistance, high temperature resistance, high anion and cation exchange capacity, and strong pigment adsorption performance, and can be widely used in food processing fields such as sugar decolorization.
[0005] Meanwhile, this invention provides an application of a macroporous weak base anion exchange resin with high abrasion resistance and permeation strength in sugar decolorization and desalination.
[0006] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows: A high-wear-resistant and high-permeability macroporous weak-base anion exchange resin is disclosed. The resin is a polystyrene ion exchange resin. The resin main chain contains acrylic spacer groups, and the functional groups for ion exchange are tertiary ammonium anion exchange groups containing nitrogen heterocycles. The resin is doped with hexagonal boron nitride particles.
[0007] Preferably, hexagonal boron nitride is bonded to the resin matrix via nitrogen-containing heterocycles.
[0008] A method for preparing a macroporous weakly basic anion exchange resin with high wear resistance and permeation strength includes the following steps: Step a) Disperse hexagonal boron nitride in deionized water, add nitrogen-containing heterocyclic compound and polymerization inhibitor, stir for 30-40 min, react at 25-60℃ for 1.5-4 h, centrifuge to obtain nitrogen-containing heterocyclic modified hexagonal boron nitride; Step b): Prepare an aqueous phase containing a dispersant and a metal salt. Mix nitrogen-containing heterocyclic modified hexagonal boron nitride, styrene, acrylic acid, crosslinking agent, pore-forming agent, and initiator evenly to obtain an oil phase reaction solution. Add the oil phase reaction solution to the aqueous phase while stirring. Heat to 50-60℃ and stir for 30-60 min. Heat to 70-85℃ and react for 1-2.5 h. Heat to 85-95℃ and react for 4-8 h. After filtration, washing, extraction, drying, and sieving (sieving to obtain ion exchange resin white spheres with a particle size range of 0.4-0.8 mm), ion exchange resin white spheres are obtained. Step c) Add the white ion exchange resin balls to chloromethyl ether, slowly (dropwise) add the catalyst, stir the reaction for 2-5 h, filter, wash, and obtain chloromethylated resin; Step d): Add the chloromethylated resin to the alkaline solution and dimethylamine solution, heat to 30-60℃, react for 1-6 h, filter, wash until neutral, and obtain macroporous weak base anion exchange resin.
[0009] Preferably, the mass ratio of hexagonal boron nitride to nitrogen-containing heterocyclic compound in step a) is 0.067~0.16:1, and the mass ratio of hexagonal boron nitride to deionized water is 0.02:1.
[0010] Preferably, the nitrogen-containing heterocyclic compound in step a) is N-vinylimidazolium or N-vinylpyridinium ketone, the polymerization inhibitor is hydroquinone or p-hydroxyanisole, and the mass ratio of the polymerization inhibitor to the nitrogen-containing heterocyclic compound is 0.03~0.05:1.
[0011] Preferably, the dispersant in the aqueous phase in step b) is polyvinyl alcohol or gelatin, the metal salt is sodium chloride, potassium chloride or magnesium chloride, and the mass ratio of dispersant, metal salt and deionized water in the aqueous phase is 1:(0.4~0.75):(117~130).
[0012] Preferably, in step b), the initiator in the oil phase reaction solution is one of benzoyl peroxide, ammonium persulfate, and azobisisobutyronitrile; the crosslinking agent is a combination of divinylbenzene and triallyl isocyanurate; the pore-forming agent is one of isobutanol, isopropanol, and polyethylene wax; the mass ratio of styrene, nitrogen-containing heterocyclic modified hexagonal boron nitride, acrylic acid, crosslinking agent, pore-forming agent, and initiator in the oil phase reaction solution is 1:(0.1~0.2):(0.05~0.06):(0.07~0.1):(0.5~0.7):(0.02~0.06); and the mass ratio of the oil phase to the aqueous phase is 1:(29~34).
[0013] Preferably, the washing process described in step b) is washing with hot water and ethanol, and the solvent used for extraction is toluene or dichloroethane.
[0014] Preferably, the catalyst in step c) is one or a combination of two of anhydrous zinc chloride, anhydrous ferric chloride, and concentrated sulfuric acid, and the mass ratio of ion exchange resin white balls, chloromethyl ether, and catalyst is 1:(0.5~1):(0.2~0.25). The washing is performed sequentially with hydrochloric acid and deionized water until neutral.
[0015] Preferably, the alkaline solution mentioned in step d) is one of sodium hydroxide and potassium hydroxide, the mass fraction of the alkaline solution is 20~30%, and the mass ratio of chloromethylated resin, alkaline solution and dimethylamine is 1:(1~1.2):(0.5~0.8).
[0016] A high-wear-resistant and high-permeability macroporous weak-base anion exchange resin, wherein the material is a polystyrene ion exchange resin, the resin main chain contains acrylic spacer groups, the ion exchange functional groups are nitrogen-containing heterocyclic tertiary ammonium anion exchange groups, and the resin is doped with hexagonal boron nitride particles.
[0017] Hexagonal boron nitride is bonded to the resin matrix through nitrogen-containing heterocycles.
[0018] A macroporous weakly basic anion exchange resin with high wear and permeation resistance is disclosed, wherein a nitrogen-containing heterocyclic compound is intercalated into hexagonal boron nitride. This invention yields a core-shell structure resin with the aforementioned nitrogen-containing heterocyclic compound and hexagonal boron nitride intercalation structure as the core and styrene resin as the shell. The styrene resin backbone contains acrylic acid spacer groups.
[0019] A macroporous weakly basic anion exchange resin with high wear resistance and permeation strength has an anion mass exchange capacity of 4.8–5.6 mmol / g, a cation adsorption rate of 77.4–85.9%, a reinforced permeation sphericity of 95.3–98.4%, a temperature resistance of 1.2–1.6%, a decolorization rate of 86.3–89.1%, and a decolorization rate constant of 0.25–0.30 min. -1 .
[0020] Application of a high-abrasion-resistant and high-permeability macroporous weak-base anion exchange resin in decolorization and desalination in the food processing and food fermentation industries.
[0021] Application of a high-wear-resistant and high-permeability macroporous weak-base anion exchange resin in sugar decolorization and desalination.
[0022] Application of a high-abrasion-resistant and high-permeability macroporous weak-base anion exchange resin in the decolorization and desalination of xylitol and sucrose.
[0023] The present invention has the following beneficial effects: (1) This invention introduces flexible acrylic groups into the styrene resin skeleton through the copolymerization reaction of acrylic acid and styrene groups, thereby improving the wear resistance and penetration strength of the resin (wear resistance and penetration strength is a key indicator for characterizing the mechanical strength of ion exchange resins, reflecting the resin's ability to resist particle breakage caused by backwashing, mixing, and repeated expansion and contraction. For long-term use, it is necessary to select a resin type that combines mechanical strength and physicochemical stability. During the test, the penetration force is generated by periodic acid and alkali treatment, combined with pressure and friction applied by ceramic ball rolling. After the treated resin is dried, the broken particles are separated, and the wear resistance is quantitatively characterized by the penetration sphericity (the proportion of spherical unbroken particles); wear resistance is tested in solution, and the performance of the wear resistance test is called wear resistance and penetration strength). At the same time, a composite styrene resin is constructed with boron nitride powder as the core, which can give full play to the excellent lubrication properties of boron nitride and further improve the wear resistance and penetration strength of the resin.
[0024] (2) In this invention, a nitrogen-containing heterocyclic compound and a boron nitride intercalation structure are introduced into styrene resin as the core, so as to give full play to the strong oil absorption performance of boron nitride, construct the internal driving force for pigment adsorption from the shell to the core of the resin, and improve the resin's ability to process pigments.
[0025] (3) The weakly basic anion resin constructed in this invention has better elution characteristics than traditional strong basic anion resin, which can improve the regeneration and recycling capacity of the resin.
[0026] (4) This invention utilizes the electrostatic adsorption between nitrogen atoms in nitrogen-containing heterocyclic compounds and boron atoms in boron nitride to achieve the stripping and modification of boron nitride by nitrogen-containing heterocyclic compounds, thereby improving the dispersibility of boron nitride in resin and its binding strength with the resin. Simultaneously, the nitrogen-containing heterocyclic compounds also enhance the adsorption of Ca in the sugar solution.2+ Mg 2+ The cations have a strong chelating effect, which can remove cations from sugar solutions, avoid poisoning of anion resin groups, give the decolorizing resin excellent desalination effect, and save costs in subsequent desalination processes.
[0027] (5) Traditional styrene resins have a strong adsorption capacity for non-polar pigments, but a weak adsorption capacity for polar pigments. In terms of the crosslinking agent used in this invention, a combination of divinylbenzene and triallyl isocyanurate is employed as a crosslinking agent. Triallyl isocyanurate is used to increase the crosslinking density of the macroporous ion exchange resin and improve the strength of the resin. At the same time, triallyl isocyanurate generates polar isocyanuric acid adsorption groups in the resin pores, which improves the adsorption effect of the resin on acidic non-sugar substances and nitrogen-containing polar pigments in the sugar decolorization process, thereby enhancing the strong decolorization effect of styrene-based resins.
[0028] This invention discloses a macroporous weakly basic anion exchange resin with high abrasion resistance and penetration strength, and its preparation method. The resin is a polystyrene-based ion exchange resin. The resin backbone contains acrylic acid spacer groups, and the ion exchange functional groups are nitrogen-containing heterocyclic tertiary ammonium anion exchange groups. Hexagonal boron nitride particles are doped into the resin matrix, and these particles are bonded to the resin matrix through nitrogen-containing heterocyclic bonds. The preparation method includes: modifying hexagonal boron nitride with a nitrogen-containing heterocyclic compound; adding the nitrogen-containing heterocyclic compound-modified hexagonal boron nitride to an ion exchange resin suspension polymerization system containing acrylic acid as spacer groups and triallyl isocyanurate as polar crosslinking groups to obtain resin white spheres; and finally, obtaining a macroporous weakly basic anion exchange resin with high abrasion resistance and penetration strength through chloromethylation and tertiary amination. This resin possesses excellent abrasion resistance and penetration strength, high temperature resistance, high anion and cation exchange capacity, and strong pigment adsorption performance, and can be widely used in food processing fields such as sugar decolorization. Attached Figure Description
[0029] Figure 1 The infrared spectrum of the macroporous weak base anion exchange resin sample from Example 1 is shown below. Figure 2 The images are SEM images of the samples from Example 1, where (a) is BN; (b) is N-vinylimidazolium-modified hexagonal boron nitride from Example 1; and (c) is a polystyrene resin slice obtained from Example 1. Figure 3 The image shows the XRD pattern of the sample from Example 1, where curve (a) represents BN and curve (b) represents N-vinylimidazolium-modified hexagonal boron nitride from Example 1. Detailed Implementation
[0030] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments. The following embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Example 1
[0031] A method for preparing a macroporous weakly basic anion exchange resin with high wear resistance and permeation strength: 2.0 g of hexagonal boron nitride was dispersed in 100 mL of deionized water, 30 g of N-vinylimidazolium and 1.0 g of p-hydroxyanisole were added, the mixture was stirred for 30 min, reacted at 25 °C for 1.5 h, and centrifuged to obtain N-vinylimidazolium-modified hexagonal boron nitride. An aqueous phase containing 40 g polyvinyl alcohol, 30 g sodium chloride, and 5000 mL deionized water was prepared. 10 g N-vinylimidazolium-modified hexagonal boron nitride, 100 g styrene, 5 g acrylic acid, 4 g divinylbenzene, 3 g triallyl isocyanurate, 50 g isobutanol, and 2 g benzoyl peroxide were mixed evenly to obtain an oil phase reaction solution. The oil phase reaction solution was added to the aqueous phase with stirring. The temperature was raised to 50 °C, and the reaction was stirred for 30 min. The temperature was then raised to 70 °C, and the reaction was carried out for 1 h. The temperature was then raised to 85 °C, and the reaction was carried out for 4 h. After filtration, washing with hot water and ethanol, extraction with toluene, drying, and sieving, ion exchange resin white spheres were obtained. Add 20 g of ion exchange resin white balls to 10 g of chloromethyl ether, slowly add 4 g of anhydrous zinc chloride, stir the reaction for 2 h, filter, and wash with hydrochloric acid and deionized water until neutral to obtain chloromethylated resin. 20 g of chloromethylated resin was added to 20 g of 20% sodium hydroxide and 10 g of dimethylamine solution, heated to 30 °C, reacted for 1 h, filtered, and washed until neutral to obtain macroporous weak base anion exchange resin.
[0032] Application of a high-wear-resistant and high-permeability macroporous weak-base anion exchange resin in the decolorization and desalination of sugars, including xylitol and sucrose.
[0033] like Figure 1 As shown, Figure 1 The medium wave number is 3434 cm⁻¹ -1 The absorption peak at 2363 cm⁻¹ corresponds to the stretching vibration peak of -OH, originating from the acrylic acid added during polymerization. -1 and 2335cm -1 The absorption peak at 1615 cm⁻¹ corresponds to the stretching vibration peak of isocyanate (-N=C=O), indicating that isocyanate groups have been introduced into the resin system. -1 The absorption peak at [location] corresponds to the stretching vibration peak of C=N, originating from the imidazole ring in N-vinylimidazolium, indicating the introduction of imidazole groups into the resin system. Simultaneously, the absorption peak at wavenumbers 1412–1476 cm⁻¹ corresponds to the peak of the stretching vibration of C=N, originating from the imidazole ring in N-vinylimidazolium. This indicates the introduction of imidazole groups into the resin system. -1 The presence of multiple absorption peaks within the range indicates the existence of various C-C bonds in the system, originating from styrene, N-vinylimidazole, and acrylic acid; simultaneously, the wavenumber is 1377 cm⁻¹. -1and 829cm -1 The absorption peaks at these locations correspond to the tensile and flexural vibration peaks of BN, respectively, indicating that BN has been introduced into the resin. In summary, this embodiment successfully introduced BN into the resin, and introduced nitrogen-containing heterocycles with imidazole groups and crosslinking groups of triallyl isocyanurate into the resin.
[0034] like Figure 2 As shown, Figure 2 (a) The BN (hexagonal boron nitride) sheets are densely packed; Figure 2 (b) The loose stacking of BN sheets indicates that after N-vinylimidazole modification in this embodiment, N-vinylimidazole intercalates into the BN sheets, causing partial peeling of the BN sheets. Figure 2 (c) is a sample image of the resin slice in this embodiment. It can be seen that boron nitride is coated with resin, thus constructing a core-shell structured ion exchange resin.
[0035] That is, the macroporous weak base anion exchange resin with high wear resistance and permeation strength obtained in this embodiment has N-vinylimidazolium intercalated in hexagonal boron nitride. This embodiment obtains a core-shell structure resin with the above-mentioned N-vinylimidazolium and hexagonal boron nitride intercalation structure as the core and styrene resin as the shell.
[0036] like Figure 3 As shown, Figure 3 (a) The BN sheets in the middle have a diffraction peak at 27.0° corresponding to the 002 crystal plane of hexagonal boron nitride. After N-vinylimidazolium modification, Figure 3 (b) The 002 crystal plane peak of the modified BN shifted to 26.8°, indicating that the interlayer spacing of BN increased after N-vinylimidazol modification, which verifies that N-vinylimidazol intercalation into BN layers. Example 2
[0037] A method for preparing a macroporous weakly basic anion exchange resin with high wear resistance and permeation strength: 4.0 g of hexagonal boron nitride was dispersed in 200 mL of deionized water, 40 g of N-vinylpyridinyl ketone and 1.5 g of hydroquinone were added, the mixture was stirred for 40 min, reacted at 45 °C for 2.5 h, and centrifuged to obtain 15 g of N-vinylpyridinyl ketone modified hexagonal boron nitride. An aqueous phase containing 50 g gelatin, 20 g potassium chloride, and 6000 mL deionized water was prepared. 15 g N-vinylpyridinone-modified hexagonal boron nitride, 100 g styrene, 6 g acrylic acid, 5 g divinylbenzene, 4 g triallyl isocyanurate, 60 g isopropanol, and 4 g benzoyl peroxide were mixed evenly to obtain an oil phase reaction solution. The oil phase reaction solution was added to the aqueous phase with stirring. The temperature was raised to 55 °C, and the reaction was stirred for 40 min. The temperature was raised to 75 °C, and the reaction was carried out for 2 h. The temperature was raised to 85 °C, and the reaction was carried out for 5 h. After filtration, washing with hot water and ethanol, extraction with dichloroethane, drying, and sieving, ion exchange resin white spheres were obtained. Add 30 g of ion exchange resin white balls to 20 g of chloromethyl ether, slowly add 6 g of anhydrous zinc chloride and concentrated sulfuric acid, stir the reaction for 3 h, filter, and wash with hydrochloric acid and deionized water until neutral to obtain chloromethylated resin. 40 g of chloromethylated resin was added to 40 g of potassium hydroxide solution with a mass fraction of 25% and 20 g of dimethylamine solution, heated to 40 °C, reacted for 2 h, filtered, and washed until neutral to obtain macroporous weak base anion exchange resin.
[0038] A macroporous weak base anion exchange resin with high wear and permeation resistance comprises: a core-shell structure with an intercalated structure of nitrogen-containing heterocyclic compound and hexagonal boron nitride as the core and styrene resin as the shell, wherein the styrene resin main chain contains acrylic spacer groups; the styrene resin main chain is also connected to tertiary ammonium anion exchange groups containing nitrogen-containing heterocyclic functional groups for ion exchange.
[0039] Application of a high-wear-resistant and high-permeability macroporous weak-base anion exchange resin in the decolorization and desalination of sugars, including xylitol and sucrose. Example 3
[0040] A method for preparing a macroporous weakly basic anion exchange resin with high wear resistance and permeation strength: 6.0 g of hexagonal boron nitride was dispersed in 300 ml of deionized water, 50 g of N-vinylimidazol and 1.5 g of hydroquinone were added, the mixture was stirred for 40 min, reacted at 45 °C for 2.5 h, and centrifuged to obtain 15 g of N-vinylimidazol modified hexagonal boron nitride. An aqueous phase containing 50 g gelatin, 25 g potassium chloride, and 6500 mL deionized water was prepared. 20 g N-vinylimidazolium-modified hexagonal boron nitride, 120 g styrene, 7 g acrylic acid, 6 g divinylbenzene, 6 g triallyl isocyanurate, 65 g isobutanol, and 5 g ammonium persulfate were mixed thoroughly to obtain an oil phase reaction solution. This oil phase reaction solution was added to the aqueous phase with stirring. The mixture was heated to 60 °C and stirred for 45 min. The temperature was then increased to 80 °C and reacted for 2.5 h. Finally, the temperature was increased to 90 °C and reacted for 6 h. After filtration, washing with hot water and ethanol, extraction with toluene, drying, and sieving, white ion exchange resin spheres were obtained. Add 40 g of white ion exchange resin balls to 40 g of chloromethyl ether, slowly add 10 g of anhydrous ferric chloride, stir and react for 4 h, filter, and wash with hydrochloric acid and deionized water until neutral to obtain chloromethylated resin. 50 g of chloromethylated resin was added to 50 g of 30% sodium hydroxide and 30 g of dimethylamine solution, heated to 50 °C, reacted for 3 h, filtered, and washed until neutral to obtain macroporous weak base anion exchange resin.
[0041] A macroporous weak base anion exchange resin with high wear and permeation resistance comprises: a core-shell structure with an intercalated structure of nitrogen-containing heterocyclic compound and hexagonal boron nitride as the core and styrene resin as the shell, wherein the styrene resin main chain contains acrylic spacer groups; the styrene resin main chain is also connected to tertiary ammonium anion exchange groups containing nitrogen-containing heterocyclic functional groups for ion exchange.
[0042] Application of a high-wear-resistant and high-permeability macroporous weak-base anion exchange resin in the decolorization and desalination of sugars, including xylitol and sucrose. Example 4
[0043] A method for preparing a macroporous weakly basic anion exchange resin with high wear resistance and permeation strength: 8.0 g of hexagonal boron nitride was dispersed in 400 ml of deionized water, 50 g of N-vinylpyridinyl ketone and 2.5 g of p-hydroxyanisole were added, the mixture was stirred for 30 min, reacted at 60 ℃ for 4 h, and centrifuged to obtain 25 g of N-vinylpyridinyl ketone modified hexagonal boron nitride. An aqueous phase containing 60 g polyvinyl alcohol, 30 g magnesium chloride, and 7000 mL deionized water was prepared. 20 g N-vinylimidazolium-modified hexagonal boron nitride, 100 g styrene, 5 g acrylic acid, 5 g divinylbenzene, 3 g triallyl isocyanurate, 70 g polyethylene wax, and 6 g azobisisobutyronitrile were mixed evenly to obtain an oil phase reaction solution. This oil phase reaction solution was added to the aqueous phase with stirring. The temperature was raised to 60 °C, and the reaction was stirred for 60 min. The temperature was then raised to 85 °C, and the reaction was carried out for 2 h. Finally, the temperature was raised to 95 °C, and the reaction was carried out for 8 h. After filtration, washing with hot water and ethanol, extraction with toluene, drying, and sieving, ion exchange resin white spheres were obtained. Add 50 g of ion exchange resin white balls to 40 g of chloromethyl ether, slowly add 10 g of anhydrous ferric chloride and concentrated sulfuric acid, stir the reaction for 5 h, filter, and wash with hydrochloric acid and deionized water until neutral to obtain chloromethylated resin. 50 g of chloromethylated resin was added to 60 g of 30% potassium hydroxide and 40 g of dimethylamine solution, heated to 60 °C, reacted for 6 h, filtered, and washed until neutral to obtain macroporous weak base anion exchange resin.
[0044] A macroporous weak base anion exchange resin with high wear and permeation resistance comprises: a core-shell structure with an intercalated structure of nitrogen-containing heterocyclic compound and hexagonal boron nitride as the core and styrene resin as the shell, wherein the styrene resin main chain contains acrylic spacer groups; the styrene resin main chain is also connected to tertiary ammonium anion exchange groups containing nitrogen-containing heterocyclic functional groups for ion exchange.
[0045] Application of a high-wear-resistant and high-permeability macroporous weak-base anion exchange resin in the decolorization and desalination of sugars, including xylitol and sucrose.
[0046] Comparative Example 1
[0047] Omit the N-vinylimidazole added in step a), directly disperse 2.0 g of hexagonal boron nitride in 100 ml of deionized water, add 1.0 g of p-hydroxyanisole, stir for 30 min, react at 25 ℃ for 1.5 h, centrifuge, and the other steps are the same as in Example 1.
[0048] Comparative Example 2
[0049] Acrylic acid modification was not used. Step b) was changed to prepare an aqueous phase containing 40 g polyvinyl alcohol, 30 g sodium chloride and 5000 mL deionized water. 10 g N-vinylimidazolium-modified hexagonal boron nitride, 100 g styrene, 4 g divinylbenzene and triallyl isocyanurate combination, 50 g isobutanol and 2 g benzoyl peroxide were mixed evenly to obtain an oil phase reaction solution. The oil phase reaction solution was added to the aqueous phase with stirring, the temperature was raised to 50 °C, and the reaction was stirred for 30 min. The temperature was raised to 70 °C and the reaction was carried out for 1 h. The temperature was raised to 85 °C and the reaction was carried out for 4 h. After filtration, washing with hot water and ethanol, extraction with toluene, drying and sieving, ion exchange resin white balls were obtained. Other steps were the same as in Example 1.
[0050] Comparative Example 3
[0051] In step b), triallyl isocyanurate is not added when synthesizing the resin white balls, and the other steps are the same as in Example 1.
[0052] Comparative Example 4
[0053] The preparation process of N-vinylimidazolium-modified hexagonal boron nitride in step a) is omitted. The N-vinylimidazolium-modified hexagonal boron nitride and acrylic acid added to the oil phase during the polymerization reaction of ion exchange resin are removed. The other steps are the same as in Example 1.
[0054] Comparative Example 5
[0055] The preparation process of N-vinylimidazolium-modified hexagonal boron nitride in step a) is omitted. The preparation process of the ion exchange resin white spheres is modified as follows: Prepare an aqueous phase containing 60 g polyvinyl alcohol, 30 g magnesium chloride and 7000 mL deionized water. Mix 100 g styrene, 5 g acrylic acid, 5 g divinylbenzene, 3 g triallyl isocyanurate, 70 g polyethylene wax and 6 g azobisisobutyronitrile to obtain an oil phase reaction solution. Add the oil phase reaction solution to the aqueous phase with stirring. Heat to 60 °C and stir for 60 min. Heat to 85 °C and react for 2 h. Heat to 95 °C and react for 8 h. Add 17 g N-vinylimidazolium and 3 g hexagonal boron nitride and stir for 4 h. After filtration, washing with hot water and ethanol, extraction with toluene, drying and sieving, the ion exchange resin white spheres are obtained. Other steps are the same as in Example 1.
[0056] That is, this comparative example did not obtain a core-shell structured resin, but only a styrene resin-supported N-vinylimidazolium-hexagonal boron nitride composite resin.
[0057] Comparative Example 6
[0058] Replace N-vinylimidazole with acrylic acid in step a), and the other steps are the same as in Example 1.
[0059] Performance testing and results:
[0060] The following performance tests were performed on the resins prepared in the above embodiments and comparative examples: 1) The anion exchange capacity of the prepared resin was determined according to the national standard (GB / T 5760-2000).
[0061] 2) The test method for cation adsorption capacity is as follows: Take 5 g of resin and add it to 100 mL of Ca-containing solution. 2+ and Mg 2+ An aqueous solution (each ion has a mass fraction of 0.5%) was used for adsorption under stirring for 5 min. After filtering to remove the resin, the total content of metal ions in the aqueous solution was tested, and the cation adsorption rate was calculated.
[0062] 3) The abrasion resistance of the resin is expressed by the enhanced abrasion sphericity. The test method for enhanced abrasion sphericity is based on the abrasion sphericity determination method - national standard GB / T 12598-2001, with the following improvements: ① The number of acid and alkali treatments on the resin is changed from 5 times to 10 times; ② For styrene-based strong base anion exchange resins, the number of ceramic balls is changed to 20; ③ The tumbling time is changed to 60 minutes.
[0063] 4) The temperature resistance of the resin is referenced in DL / T 953-2005. After heating in a 95℃ water bath for 100 h, the decrease rate of anion exchange capacity is tested.
[0064] 5) The decolorization rate was tested by adding 0.5 g of resin to a mixed solution containing 10 mL of caramel pigment with an initial mass concentration of 50 mg / L and 10 mL of melanin with an initial mass concentration of 50 mg / L. The solution was then shaken at 120 rpm for 2 h in a water bath at 25°C. The absorbance of the pigment solution before and after adsorption was measured, and the decolorization rate was calculated.
[0065] 6) The decolorization rate was tested by adding 0.5 g of resin to a mixed solution containing 10 mL of caramel pigment with an initial mass concentration of 50 mg / L and 10 mL of melanin with an initial mass concentration of 50 mg / L. The solution was shaken at 120 rpm in a water bath at 25°C. The absorbance of the pigment solution before and after adsorption was measured every 5 min. The measured absorbance values were substituted into the corresponding standard curve to obtain the dye concentration C0 before adsorption and the residual dye concentration C at each sampling point after adsorption. A kinetic curve was plotted with the sampling time point t as the abscissa and ln(C0 / C) as the ordinate. The curve was linearly fitted, and the slope of the fitted line was the decolorization rate constant.
[0066] The test results of the resins prepared in the examples and comparative examples are shown in Table 1 below.
[0067] Table 1
[0068] It should be understood that, in order to simplify this disclosure and aid in understanding one or more of the various aspects of the invention, features of the invention are sometimes grouped together in a single embodiment, figure, or description thereof in the above description of exemplary embodiments of the invention. However, this method of disclosure should not be interpreted as reflecting an intention that the claimed invention requires more features than expressly recited in each claim. Rather, as reflected in the claims, inventive aspects lie in fewer than all the features of the foregoingly disclosed embodiments. Therefore, the claims, following the detailed description, are hereby expressly incorporated into that detailed description, wherein each claim itself is a separate embodiment of the invention.
[0069] Although the invention has been described with reference to a limited number of embodiments, those skilled in the art will understand from the foregoing description that other embodiments are conceivable within the scope of the invention described herein. Furthermore, it should be noted that the language used in this specification has been chosen primarily for readability and instructional purposes, and not for the purpose of interpreting or limiting the subject matter of the invention. Therefore, many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the appended claims. The disclosure of the invention is illustrative and not restrictive, and the scope of the invention is defined by the appended claims.
[0070] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A macroporous weakly basic anion exchange resin with high wear resistance and permeation strength, characterized in that, include: A core-shell structure with a nitrogen-containing heterocyclic compound and hexagonal boron nitride intercalation structure as the core and styrene resin as the shell, the styrene resin backbone contains acrylic spacer groups; the styrene resin backbone is also connected to tertiary ammonium anion exchange groups containing nitrogen-containing heterocyclic compounds for ion exchange. The preparation method includes: modifying hexagonal boron nitride with nitrogen-containing heterocyclic compounds, adding hexagonal boron nitride modified with nitrogen-containing heterocyclic compounds to an ion exchange resin suspension polymerization system containing acrylic acid as a spacer group and triallyl isocyanurate as a polar crosslinking group to obtain resin white spheres; and finally obtaining a macroporous weak base anion exchange resin with high wear resistance and permeation strength through chloromethylation and tertiary amination. The nitrogen-containing heterocyclic compound is N-vinylimidazolium or N-vinylpyridinyl ketone.
2. The high abrasion resistance and permeation strength macroporous weak base anion exchange resin according to claim 1, characterized in that, Its anion exchange capacity is 4.8–5.6 mmol / g, its cation adsorption rate is 77.4–85.9%, its enhanced infiltration and milling sphericity is 95.3–98.4%, its decolorization rate is 86.3–89.1%, and its decolorization rate constant is 0.25–0.30 min. -1 .
3. The method for preparing a high-wear-resistant, high-permeability macroporous weak-base anion exchange resin according to claim 1 or 2, characterized in that, Includes the following steps: Step a) Disperse hexagonal boron nitride in deionized water at a mass ratio of 0.02:1; add a nitrogen-containing heterocyclic compound and a polymerization inhibitor at a mass ratio of 0.067~0.16:1 and a mass ratio of 0.03~0.05:1; stir for 30~40 min; react at 25~60℃ for 1.5~4 h; centrifuge to obtain nitrogen-containing heterocyclic modified hexagonal boron nitride. Step b): Prepare an aqueous phase containing a dispersant and a metal salt. The mass ratio of dispersant, metal salt, and deionized water in the aqueous phase is 1:(0.4~0.75):(117~130). Mix nitrogen-containing heterocyclic modified hexagonal boron nitride, styrene, acrylic acid, crosslinking agent, pore-forming agent, and initiator evenly to obtain an oil phase reaction solution. The mass ratio of styrene, nitrogen-containing heterocyclic modified hexagonal boron nitride, acrylic acid, crosslinking agent, pore-forming agent, and initiator in the oil phase reaction solution is 1:(0.1~0.2):(0.05~0.06):(0.07~0.1):(0.5~0.7):(0.02~0.06), and the mass ratio of oil phase to aqueous phase is 1:(29~34). Add the oil phase reaction solution to the aqueous phase with stirring, heat to 50~60℃, stir for 30~60 min, heat to 70~85℃, and react for 1~2.5 minutes. h, heat to 85~95℃, react for 4~8 h, and after filtration, washing, extraction, drying and sieving, obtain ion exchange resin white balls; Step c) Add the white ion exchange resin balls to chloromethyl ether, and slowly add the catalyst. The mass ratio of the white ion exchange resin balls, chloromethyl ether, and catalyst is 1:(0.5~1):(0.2~0.25). Stir the reaction for 2~5 h, filter, wash, and obtain chloromethylated resin. Step d): Add chloromethylated resin to alkaline solution and dimethylamine solution. The mass fraction of alkaline solution is 20-30%, and the mass ratio of chloromethylated resin, alkaline solution and dimethylamine is 1:(1-1.2):(0.5-0.8). Heat to 30-60℃ and react for 1-6 h. Filter and wash until neutral to obtain macroporous weak base anion exchange resin.
4. The preparation method according to claim 3, characterized in that, In step a), the polymerization inhibitor is hydroquinone or p-hydroxyanisole.
5. The preparation method according to claim 3, characterized in that, In step b), the dispersant in the aqueous phase is polyvinyl alcohol or gelatin, and the metal salt is sodium chloride, potassium chloride, or magnesium chloride.
6. The preparation method according to claim 3, characterized in that, In step b), the initiator in the oil phase reaction solution is one of benzoyl peroxide, ammonium persulfate, and azobisisobutyronitrile; the crosslinking agent is a combination of divinylbenzene and triallyl isocyanurate; and the pore-forming agent is one of isobutanol, isopropanol, and polyethylene wax.
7. The preparation method according to claim 3, characterized in that, In step b), the washing process involves washing with hot water and ethanol, and the solvent used for extraction is toluene or dichloroethane.
8. The preparation method according to claim 3, characterized in that, In step c), the catalyst is one or a combination of two of anhydrous zinc chloride, anhydrous ferric chloride, and concentrated sulfuric acid; the washing is performed sequentially with hydrochloric acid and deionized water until neutral.
9. The preparation method according to claim 3, characterized in that, In step d), the alkaline solution is either sodium hydroxide or potassium hydroxide.
10. The application of a high-abrasion-resistant, high-permeability macroporous weak-base anion exchange resin according to claim 1 or 2 in the decolorization and desalination of sugars, characterized in that, Sugars include xylitol and sucrose.
Citation Information
Patent Citations
Prepreg prepared from boron nitride modified by continuous method and high-thermal-conductivity thermosetting high-frequency copper-clad plate
CN114437489A
Boron nitride powder, resin composition, and method for producing boron nitride powder
CN118660861A